Analisis Potensial Tiongkok Untuk Menjadi Negara Hegemon di Kawasan Asia Timur Melalui Strategi One Belt One Road - Harahap, Fathin Nisa Muthia; Susiatiningsih, Rr. Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This research seeks is to know the potential of China to become a hegemonic country in East Asian region through the One Belt One Road strategy that initiated by China. This research uses the theory of offensive realism and the concept of hegemony to explain about China OBOR and China Foreign Policy. So based on this, the result of this study show that through the OBOR strategy that known as the Xi Jinping main Foreign Policy, China can improve the country’s economy and military expenditure, which is that two main aspect is the reason why state become a hegemonic country. So, that one of the requirement of the existing hegemon state in the hegemony concept has been fulfilled by China by improving their economic and military growth. And some response from neighboring China in East Asia region indicate that there are hegemony efforts that have been carried out by China through its OBOR strategy.